„Siadaj i opowiadaj mi, co tam u ciebie na warsztacie”. O Profesorze Jerzym Starnawskim z profesor Marią Wichową rozmawiają Tomasz Cieślak i Michał Kuran - Cieślak, Tomasz; Kuran, Michał; Kałowska, Agnieszka (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2013)
Interview with professor Maria Wichowa on Professor Jerzy Starnawski, long-term head of the Department of Old Polish Literature at the University of Łódź, who died in 2012. As a former student of the Professor, she discusses issues such as the origins of scholarly interests of her teacher, his love of Latin and Romanticism literature, his methods of work with students and doctoral candidates, and his the organizational talents.